Opto-VLSI-based beamformer for radio-frequency phased-array antennas - Xiao, F.; Juswardy, Budi; Alameh, K.; Xiao, S.; Hu, W. (2012)
An Opto-VLSI-based tunable beamformer for radio frequency (RF) smart antennas is reported and its concept is demonstrated. RF beam steering is achieved by uploading appropriate phase holograms onto the Opto-VLSI processor so that RF true-time delays (TTDs) are independently generated for each element of the antenna array by simply using several erbium-doped fiber amplifier (EDFA) loops to realize independent tunable fiber lasers in conjunction with a dispersive optical fiber. Experimental results demonstrate RF beam steering up to 30deg; with a 4-element linear patch antenna array operating at 1.85 GHz. © 2012 IEEE.